2013
DOI: 10.1002/ange.201208038
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Damage Following Radiation‐Induced Oxidation of Uracil in Aqueous Solution

Abstract: Coulomb‐Explosion an Uracil: Ionisierende Strahlung kann im Zuge der Krebstherapie gezielt molekulare Schäden in Zellen hervorrufen. Frühe Dissoziationsprozesse und chemische Folgereaktionen nach einer selektiven Ionisierung von Uracil oder umgebenden Wassermolekülen (siehe Schema: C grau, N blau, O rot, H weiß) wurden mithilfe von Ab‐initio‐Moleküldynamik untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Production of excited species from a water molecule by charge transfer reaction with doubly charged UMP ion is supposed to give rise to a much more energetic luminescence. The proposed charge transferring reaction between doubly charged UMP ion and a water molecule producing singly charged excited parent ion of UMP, with transfer of a single positive charge (e.g., a proton) to the hydrating water, is supported by previous reports (Lopez-Tarifa et al 2013, Fujii et al 2018. We have thus tentatively concluded that the present luminescence of aqueous UMP is due to singly charged parent ion species of UMP produced by the emission of a proton from doubly charged ions following Auger ionization of a N 1 s electron in uracil moiety.…”
Section: Resultssupporting
confidence: 78%
“…Production of excited species from a water molecule by charge transfer reaction with doubly charged UMP ion is supposed to give rise to a much more energetic luminescence. The proposed charge transferring reaction between doubly charged UMP ion and a water molecule producing singly charged excited parent ion of UMP, with transfer of a single positive charge (e.g., a proton) to the hydrating water, is supported by previous reports (Lopez-Tarifa et al 2013, Fujii et al 2018. We have thus tentatively concluded that the present luminescence of aqueous UMP is due to singly charged parent ion species of UMP produced by the emission of a proton from doubly charged ions following Auger ionization of a N 1 s electron in uracil moiety.…”
Section: Resultssupporting
confidence: 78%
“…The RT-TDDFT approach is mostly used in the context of linear and nonlinear spectroscopies, 7,44,51−54 yet its scope was extended toward computational photodynamics. 14 It was used in order to investigate dynamics following Auger decay in water or nucleic acid bases, 55,56 to model low energy collisions between atoms and molecules, 57 radiation damage in materials, 58 or stopping power in the context of hadron therapies, 59−61 and for observing charge migration in molecules and dye-sensitized materials. 62,63 RT-TDDFT is on the other hand no panacea, and there are several issues to be addressed.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To further investigate the early chemical reactions of the fragments within the sample, we switched to ground-state CP MD with a time step of 0.006 fs for a total simulation length of 1.3 ps. 15 When switching from TDDFT to CP MD, the positions and the velocities of all the atoms are kept unchanged, while the electronic structure is optimized to reach the BO surface, leading to a slight redistribution of the electronic cloud.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Indeed, the multitude of doubly ionized states are expected to be close in energy leading to fast nonadiabatic switches, which can quickly drive the system to the ground state. The dissociation of doubly ionized water 11 and uracil 15 molecules solution as well as isolated uracil 16 has already been reported.…”
Section: ■ Introductionmentioning
confidence: 91%